Analysis of Influencing Factors of a Fully Enclosed Double-Cylinder CO2 Rotor Expander for Air-Conditioner - Wang, Pai; Li, Minxia; Ma, Yitai; Tian, Hua; Hou, Beiran (Frontiers in Energy Research, 2022)
CO2 household air-conditioners are difficult to popularize due to their low efficiency. The use of the expander can reduce the throttling loss and increase the cooling capacity of the CO2 system. In this paper, a fully enclosed double-cylinder rotor expander is designed. The structure and working progress are introduced. The factors affecting the efficiency of the expander are theoretically analyzed. The results show that the design of high back pressure can greatly improve the efficiency. Moreover, the relative cylinder height of the first cylinder should be between 0.2 and 0.3, while the relative cylinder height of the second cylinder should be between 0.4 and 0.6. The relative eccentricity should be around 0.1. The expander is very suitable for the condition of high outlet temperature of the gas cooler. There is a peak mass flow rate when the efficiency of the expander is maximum. This paper provides theoretical support for the design and manufacture of expander.